Peritoneal carcinomatosis in gastric cancer: Are Hispanics at higher risk?. Issue 8 (9th September 2020) - Choi, Audrey H.; Ji, Liang; Babcock, Blake; Ramos, Vicente; Kwong, Mei Li M.; Morgan, John W.; Selleck, Matthew J.; Langridge, William H. R.; DeLeon, Marino; Wall, Nathan R.; Lum, Sharon; Pigazzi, Alessio; et al.
Abstract: Background: A recent study from our group identified Hispanic race/ethnicity as an independent predictor of peritoneal carcinomatosis (PC) in gastric cancer. We sought to identify the tumor factors that might contribute to this strong association in Hispanics. Methods: California Cancer Registry data were used to identify patients diagnosed with gastric adenocarcinoma from 2004 to 2014. Logistic regression analyses were performed to determine odds ratios for cancer stage, tumor location, grade, histology, and PC. Results: Of 16, 275 patients with gastric adenocarcinoma who met inclusion criteria, 6463 (39.7%) were non‐Hispanic White (NHW), 4953 (30.4%) were Hispanic, 1020 (6.3%) were non‐Hispanic Black (NHB), and 3915 (23.6%) were Asian/other. Compared to NHW, Hispanics were more likely to have a poorly differentiated grade (65.9% vs. 57.6%; p  < .001), signet ring adenocarcinoma (28.1% vs. 17.6%; p  < .001) and stage IV (51.9% vs. 45.0%; p  < .001) gastric cancer. The proportion of stage IV patients with PC was also significantly higher in Hispanics compared to NHW, NHB, and Asian/other (28.5% vs. 16.6%, 20.5%, and 25.2%, respectively; p  < .001). Conclusions: Hispanic ethnicity is an independent predictor of aggressive tumor phenotype and PC. Disproportionate incidence of signet ring adenocarcinoma and PC highlight the need to explore the genomic differences in Hispanic gastric cancer.